Calm on the surface, dynamic on the inside. Molecular homeostasis in response to regulatory and metabolic perturbation of Anabaena sp. PCC 7120 nitrogen metabolism - Perin,G; Fletcher,T; Sagi-Kiss,V; Gaboriau,DCA; Carey,MR; Bundy,JG; Jones,PR (2020)
Abstract Nitrogen is a key macro-nutrient required for the metabolism and growth of biological systems. Although multiple nitrogen sources can serve this purpose, they are all converted into ammonium/ammonia as a first step of assimilation. It is thus reasonable to expect that molecular parts involved in the transport of ammonium/ammonia across biological membranes (i.e. catalysed by AMT transporters) connect with the regulation of both nitrogen and central carbon metabolism. In order to test this hypothesis, we applied both (1) genetic (i.e. Δ amt mutation) and (2) environmental treatments to a target biological system, the cyanobacterium Anabaena sp. PCC 7120. Cyanobacteria have a key role in the global nitrogen cycle and thus represent a useful model system. The aim was to both (1) perturb sensing and low-affinity uptake of ammonium/ammonia and (2) induce multiple inner N states, followed by targeted quantification of key proteins, metabolites and enzyme activities, with experiments intentionally designed over a longer time-scale than the available studies in literature. We observed that the absence of AMT transporters triggered a substantial response at a whole-system level, affecting enzyme activities and the quantity of both proteins and metabolites, spanning both N and C metabolism. Moreover, the absence of AMT transporters left a molecular fingerprint indicating N-deficiency even under N replete conditions (i.e. greater GS activity, lower 2-OG content and faster nitrogenase activation upon N deprivation). Contrasting with all of the above dynamic adaptations was the striking near-complete lack of any externally measurable phenotype (i.e. growth, photosynthesis, pigments, metabolites). We thus conclude that this species evolved a highly robust and adaptable molecular network to maintain homeostasis